2006
DOI: 10.1179/oeh.2006.12.4.346
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health in Mexico

Abstract: This article describes the current situation of occupational health (OH) in Mexico, including socioeconomic context, legislation, health system, and educative and investigative resources, as well as the practice of OH. Workplace accidents per 100 workers decreased from 7.23 to 2.3 workers in 20 years; deaths decreased from 1.68 to 0.9 per 10,000 workers, while the occupational disease rate increased from 0.6 to 1 per 10,000 workers. This can be interpreted as an improvement in preventive measures as well as pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 5 publications
1
11
0
3
Order By: Relevance
“…Meanwhile, other studies have suggested that factors related to companies [ 26 ], especially organizational and normative aspects [ 27 ], could be even more relevant to the lethality of an injury than individual factors. The objective of this study is to identify the factors associated with fatality in the event of an occupational injury at the national level in Mexico using the Occupational Risk Information System database from the IMSS [ 28 , 29 ]…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, other studies have suggested that factors related to companies [ 26 ], especially organizational and normative aspects [ 27 ], could be even more relevant to the lethality of an injury than individual factors. The objective of this study is to identify the factors associated with fatality in the event of an occupational injury at the national level in Mexico using the Occupational Risk Information System database from the IMSS [ 28 , 29 ]…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, job insecurity and unemployment, which have also been associated with poor health [Virtanen et al, ], are highly prevalent in this country [Noriega‐Elío et al, ]. Mexico's current economic crisis has forced workers to start jobs in the informal economy (approximately 28% of the economically active population worked in the informal sector by the end of 2011 [Instituto Nacional de Estadística y Geografía, ]) or to emigrate to the United States [Sanchez‐Roman et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…IMSS covers most of the formal sector of the economy. However, the informal sector has grown rapidly during the last decades so that above figures solely reflect the reality of occupational accidents in 30% of the workers [Sánchez-Román et al, 2006]. If we apply the rates of the population covered by IMSS to the total workforce, assuming similar occupational risks, we can estimate that 1.4 million workrelated injuries occur each year in the country.…”
Section: Discussionmentioning
confidence: 99%